SISTEM MANAJEMEN MADRASAH IBTIDAIYAH NEGERI DI KOTA PADANG - Abdul Basit; Martin Kustati; Nana Sepriyanti (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to describe the management of public elementary schools in the city of Padang. The research method used is descriptive qualitative. The research subjects were the head of the madrasa, students, teachers and parents. Data collection techniques used are observation, interviews, and documentation. Data analysis techniques include data reduction, data display, verification and conclusions. The results of this study explain that program planning has supported madrasah activities, teacher subjects that are relevant to their educational background, develop curricula effectively and efficiently, students participate in talent, competence, and motivational activities, school finances are budgeted every year where all madrasah components authorized to control the use of finances, use madrasa facilities and infrastructure that support the teaching and learning process, parental participation in madrasas.